Mapping and validating new climate smart agriculture (CSA) technologies and climate information services (CIS) in Ghana. - Yeboah, Stephen; Adomako, Joseph; Narveh, Ernestina; Amankwa-Yeboah, Patricia; Frimpong-Anin, Kofi; Haleegoah, Joyce; Adablah, Richard (2024)
Food crop producing zones are encountering numerous challenges including unpredictable weather patterns characterized by droughts and floods, soil degradation due to inadequate conservation practices, limited access to mechanization, pests and diseases and insufficient utilization of Agro-advisories. At the same time, arable land and other production resources are limited, and area expansion for food production is not appropriate or recommended in the spate of urbanization and multiple land uses. With extensive urbanization and competition for farmlands for other projects, any increase in crop production should be met mainly by increased productivity i.e., improved crop yields per unit area than the increase in cultivated areas. Sustainable food production technology is imperative to curb food insecurity, reduce poverty, and impact the livelihood of smallholder farmers. Ghana is highly vulnerable to climate variability and change, which continues to pose a threat to future growth and development. Resilience must therefore be built into its food systems to reduce the vulnerability of smallholder farmers. The promotion and uptake of validated new climate smart agriculture (CSA) technologies and climate information services (CIS) in Ghana through capacity strengthening, demonstration, and awareness creation is important to reducing the current challenges militating against food crop production